Depressão em portadores do vírus da imunodeficiência humana em uma unidade de referência: Belém, Pará - OLIVEIRA, Edgar Luis Lima de (2023)
This survey was carried out from November 2007 to January 2009, with the aim to know the prevalence of major depressive disorder in sample of patients with human immunodeficiency virus infection seen at the Reference Center for Parasitic and Infectious Special Diseases, in the city of Belém, Pará, as well as to describe aspects of their sociodemographic and clinical features, to investigate if depression is associated with CD4+ T lymphocytes counts and with the use of antiretroviral drugs, and to describe the symptoms from those who had depression. The epidemiologic study design used was cross-sectional. 115 subjects were submitted to an interview in order to obtain information about sociodemographic and clinical features and assessed for depression using the MINI International Neuropsychiatric Interview. The participants identified with current major depression were also evaluated with the sub-scale of depression of the Hospital Anxiety and Depression Scale and with the Beck Depression Inventory. The statistics analysis was carried out in the EPI INFO program version 6.04. The prevalence of depression found was 31,3%. There was no predominant sex; most of the individuals were between 30 and 50 years old (74.8%), were heterosexual (65.2%), had only incomplete primary school (39.1%), received some benefit from the government (33.0%) and lived in Belém (58.3%). The majority of the participants (77.7%) had the diagnosis of the infection for more than one year before the interview; 76.5% were using antiretroviral drugs and 60.9% had CD4+ T lymphocytes counts under 350 cells/mm3. Depression was not associated to levels of CD4+ T lymphocytes, nor to the use of antiretroviral drugs. The most frequent symptoms in those identified with current major depression were sadness, self-criticalness, fatigue, irritability, change in sleep patterns and somatic concern. The prevalence of depression and bipolar affective disorder was very high, affecting 60% of the participants. Therefore, it is necessary that individuals infected by the human immunodeficiency virus receive special attention for these disorders, since psychiatric illnesses can compromise their quality of life, jeopardize the adherence to the antiretroviral therapy, decrease the time of survival, facilitate risky behaviors and, hence, contribute for the propagation of the virus.